The Effect of Inquiry-Based Learning on the Critical Thinking Skills of Eleventh-Grade Social Science Students in Economics - Astina; Hafid, Radia; Maruwae, Abdulrahim; Bumulo, Frahmawati; Dama, Maya Novrita (International Journal of Research in Education, 2025)
This study was conducted to highlight the importance of enhancing students' critical thinking skills through effective teaching methods. Using a quasi-experimental design with a post-test approach, the research involved 36 eleventh-grade students from MA Salafiyah Syafi'iyah, divided into an experimental group and a control group. The study aimed to examine the impact of the Inquiry-Based Learning (IBL) method on students’ critical thinking abilities in economics. Descriptive and statistical analyses were used to evaluate the data. Results showed a clear difference between the two groups: the control class had an average score of 63.89, while the experimental class, which applied the IBL method, achieved an average of 88.29. A paired samples test showed a Sig. (1-tailed) value of 6.664 > 0.005, indicating a statistically significant improvement. These findings demonstrate that the IBL method effectively enhances students' critical thinking skills compared to traditional teaching methods. The implication of this study is that adopting inquiry-based approaches in economics education can foster deeper understanding and better cognitive engagement among students.